DC-DC Converter Implementing Soft Switching Technique for AC Power Applications (Journal of Information Technology and Digital World, 2022)
Global warming alerts the world to switch over to using Electric Vehicle (EV) and Hybrid Electric Vehicles (HEV). The Bidirectional DC-DC Converter (BDC) plays a significant role in controlling the energy flow for the Battery Ultra-capacitor Energy Storage System (BUESS) which is used for storing energy in EV or HEV. The bidirectional DC-DC converter (BDC) plays a vital role in controlling the energy flow for BUESS. The bidirectional DC-DC converter performs the step-up and step-down operation at zero voltage switching, as it operates in buck and boost modes. Due to the uncertain nature of renewable energy resources they pose to be not suitable for standalone applications as the only source of power. This problem can be overcome with the aid of batteries and supercapacitors for storing energy. Fast charging is done by a supercapacitor and slow discharging by a battery. A hysteresis control loop achieves the design of charging and discharging status. A BDC in addition to an inverter can be opted and is implemented in MATLAB/Simulink, and is used in AC power applications.
Keywords: Soft-switching; Bi-directional DC/DC converter; Super capacitor; Li-Ion Battery